Planning Theory and Environmental Ethics: Towards the Integration of Biodiversity and Urban Planning - Fitrawan Umar; Haryo Winarso (Department of Urban and Regional Planning, Diponegoro University, 2022)
Planning is a forward-looking and public-interest process, and for that purpose there is a choice of actions to be taken. Communicative rationality is highly recommended in planning related to the environment. However, among the factors that influence environmental planning communication, particularly regarding biodiversity issues, environmental ethics is still rarely discussed. Various environmental ethics need to be understood by a planner as a communicator and translating the desires of interested groups. Attention to environmental ethics also helps planners in selecting appropriate approaches to integrate biodiversity into urban planning. This study aims to examine the relationship between planning theory and environmental ethics that is often overlooked in efforts to integrate biodiversity and urban planning. With the narrative literature review method, the results showed that the approach of cultural ecosystem services is one of the middle paths to bridge the variety of environmental ethics that are understood by the community and government. This approach opens a wide space for motives to conserve biodiversity in urban areas so that aspects of sustainability and human well-being can be achieved together.